Improving Sensor Network in Sustainable City - Vijayan, Vinodh P; George, Neema; Kurian, Simy Mary; Sujitha, M (International Journal of Computer Sciences and Engineering, 2019)
Lately, we've seen a twist of online internet based totally business sites. It indicates an superb threat to share our surveys and evaluations for distinctive gadgets we purchase. Looking to the score cannot the simplest one assist a client to get an define about the object as an alternative the maximum perfect course is to peruse the audits about the item. Be that as it may, at that point a captivating issue comes up. Imagine a scenario in which the quantity of surveys is within the hundreds or hundreds. Which contain of 10 to 15 pages at that factor it is virtually no longer possible to experience each one of these surveys because of wastage of time and exertion. Here comes the importance of audits. To mine profitable information from audits to recognise a patron's tendencies and make a precise cease pivotal. In this work, we recommend a sentiment based rating expectation technique to take care of this difficulty.